Postnatal undernutrition delays a key step in the maturation of hypothalamic feeding circuits - Alain Juan De Solis; Arian F. Baquero; Camdin M. Bennett; Kevin L. Grove; Lori M. Zeltser (Elsevier, 2016)
Objective: Humans and animals exposed to undernutrition (UN) during development often experience accelerated "catch-up" growth when food supplies are plentiful. Little is known about the mechanisms regulating early growth rates. We previously reported that actions of leptin and presynaptic inputs to orexigenic NPY/AgRP/GABA (NAG) neurons in the arcuate nucleus of the hypothalamus are almost exclusively excitatory during the lactation period, since neuronal and humoral inhibitory systems do not develop until after weaning. Moreover, we identified a critical step that regulates the maturation of electrophysiological responses of NAG neurons at weaning - the onset of genes encoding ATP-dependent potassium (KATP) channel subunits. We explored the possibility that UN promotes subsequent catch-up growth, in part, by delaying the maturation of negative feedback systems to neuronal circuits driving food intake. Methods: We used the large litter (LL) size model to study the impacts of postnatal UN followed by catch-up growth. We evaluated the maturation of presynaptic and postsynaptic inhibitory systems in NAG neurons using a combination of electrophysiological and molecular criteria, in conjunction with leptin's ability to suppress fasting-induced hyperphagia. Results: The onset of KATP channel subunit expression and function, the switch in leptin's effect on NAG neurons, the ingrowth of inhibitory inputs to NAG neurons, and the development of homeostatic feedback to feeding circuits were delayed in LL offspring relative to controls. The development of functional KATP channels and the establishment of leptin-mediated suppression of food intake in the peri-weaning period were tightly linked and were not initiated until growth and adiposity of LL offspring caught up to controls. Conclusions: Our data support the idea that initiation of KATP channel subunit expression in NAG neurons serves as a molecular gatekeeper for the maturation of homeostatic feeding circuits. Author Video: Author Video Watch what authors say about their articles Keywords: NPY, AgRP, Leptin, Undernutrition, KATP channel, Feeding circuits